Avaliação dos efeitos da guanosina frente a neurotoxicidade induzida por ácido quinolínico sobre parâmetros bioquímicos e comportamentais no nematoide Caenorhabditis elegans - Silveira, Tássia Limana da (2024)
Quinolinic acid (QUIN) is an endogenous neurotoxin that acts as an agonist of the N-methyl-D-aspartate (NMDAR) receptor, generating a toxic cascade that can lead to neurodegeneration. Guanosine (GUO) is a purine nucleoside produced endogenously in physiological processes and more pronounced in pathological situations, reducing neuroinflammation, oxidative stress, and excitotoxicity. In Caenorhabditis elegans to exogenous exposure to neurotoxins that damage the glutamatergic system, such as QUIN, has been little studied. Consequently, the study of possible neuroprotective agents against damage to the glutamatergic system is not well known, and it is essential to understand them better to comprehend pathologies involving this system. The effects of QUIN (20mM) and GUO (4mM) were analyzed in wild-type animals (N2) and in transgenic animals nmr-1, nmr-2, eat-4, glr-1, glt-3, and glt-1;glt-3. The effects of QUIN and GUO on biochemical and behavioral parameters in C. elegans were analyzed. The results showed that GUO reduced pharyngeal pumps in N2 animals concentration-dependently. The same effect was observed in pharyngeal pumps when animals knocked out glr-1, nmr-1, and eat-4, but not in glt-3 and glt-3;glt-1 exposed to GUO. The double mutant glt-3;glt-1 for Glu transporters (GluT) decreased the animals' body bends and increased the number of reversals. This effect was prevented by exposure to GUO. The QUIN increased locomotor parameters modulated by Glu such as distance and time traveled in reversal, the time of 1-octanol response, brood size, reduced oxygen consumption, and mitochondrial membrane potential in an NMDAR-dependent way, decreasing the flow of electrons coupled and uncoupled with the ATP production. Moreover, GUO protected N2 animals against behavioral changes induced by QUIN, such as track length, distance and time traveled forward, number of turn count, and distance traveled in reversal. Furthermore, these protective effects are partially lost in knockout animals for the NMDAR NMR-2 and GluT the GLT-3, and GLT-1. Our results suggest that QUIN can be used as a model of glutamatergic excitotoxicity in C. elegans and GUO as a possible treatment for pathologies associated with this system.